Rationing training load according to the nature of the prevailing muscular work and its effect on the functional adaptation, specific strength and snatch achievement for weightlifters at (14-16 year-old) - Abdulwahaab Ismaeel, S.; Al-Jorani, A. K.; Al-Sudani, A. S. (Asian Exercise and Sport Science Journal, 2021)
The study aimed at identifying the nature of the prevailing muscular work for some muscular working groups in the snatch (rectus femoris muscle and deltoid or the common shoulder muscle) by adopting two indicators(electric spectrum power and muscular latency period) in order to ration the training load in the program prepared by the Certified Trainer of the Iraqi Central Weightlifting Federation. It also aimed at identifying the extend of muscle fiber adaptation by adopting(electric spectrum power , muscle latency period- peak wave - area under the curve ) according to the type of rationing used; and identifying the effect of training load rationing according to the nature of the prevailing muscular work on specific strength and snatch achievement.